Chronic pain after traumatic brain injury: a collaborative care approach - Mary C. Curran; Sylvia Lucas; Sylvia Lucas; Sylvia Lucas; Jesse R. Fann; Jennifer M. Zumsteg; Jeanne M. Hoffman (Frontiers Media S.A., 2024)
IntroductionChronic pain is common after traumatic brain injury (TBI), frequently limits daily activities, and is associated with negative outcomes such as decreased community participation. Despite the negative impact of chronic pain, few people with TBI receive effective treatment. This paper describes a collaborative care (CC) intervention, TBI Care, adapted specifically to treat chronic pain in people living with TBI, emphasizing expert clinician input, cognitive behavioral therapy (CBT) techniques, and other non-pharmacological approaches for decreasing pain interference.Methods79 participants engaged in the CC intervention from two academic medical rehabilitation clinics with weekly assessments of pain intensity, interference, and medication use. Participant feedback on the intervention was gathered by interview with the care manager (CM) at the last treatment session and/or booster session. Provider feedback was gathered by a confidential survey post intervention.ResultsNinety percent of participants received at least 11 of the target 12 sessions with a care manager (CM), the majority occurring over the phone. Participants endorsed an average of 7 pain locations. All participants received pain education, skills in self-monitoring, goal setting/behavioral activation and relaxation training. Pain interference scores (impact on activity and enjoyment), tracked weekly by the CM, significantly decreased across sessions. 89% of participants received recommendations for CBT skills, 65% received referrals for additional treatments targeting pain interference, and 43% received care coordination. 75% of participants reported 6 or more medications/supplements at both the first and last session, with changes recommended primarily for headache treatment. Feedback from participants and providers was positive.DiscussionTBI Care, a novel patient-centered CC approach, was flexibly delivered, tailored to the needs of those living with TBI and chronic pain, with a high level of participant engagement, and satisfaction among participants and providers. This approach, prioritizing pain self-management strategies and other non-pharmacological approaches, along with optimizing pharmacological treatment, led to significant reductions in self-reported pain interference and intensity during the intervention. Using a CC model in TBI is feasible and successfully improved access to evidence-based treatments for chronic pain as well as outcomes for pain interference and intensity.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT03523923.